The Influence of tawhidic paradigm in managing firms for sustainable competitive advantage: a Malaysian case - Mhd. Sarif, Suhaimi; Sarwar, Abdullah Al-Mamun; Ismail, Yusof (Leena & Luna International, Oyama, Japan, 2015)
Businesses continue to struggle to achieve sustainable competitive advantage for better profitability and strategic positioning in the competitive markets. The underpinned understanding in achieving sustainable competitive advantage is driven by organizational objectives. However, the sustainability of the business, business continuity and sustainable competitive advantage depends on both external and internal factors of the firm. Indeed, a unified theory of the firm is necessary to provide insights for rigorous, dynamic and comprehensive strategic management analyses. Hence, this study has attempted to investigate the influence of Tawhidic paradigm in managing firms’ for sustainable competitive advantage from Malaysian perspective. Data has been collected from 242 public listed companies listed in the main board of Bursa Malaysia. The respondents were asked to evaluate items from 4 different constructs through a 6 point scale varied from never, rarely, slightly, sometime, usually, and always. Furthermore, Structural Equation Modelling (SEM) has been run for exploring the relationship that exists among the different salient variables which in turn measures the influence of Tawhidic paradigm in managing firms for sustainable competitive advantage in Malaysia. Based on the results, it can be perceived that Tawhidic paradigm is to a great extent influenced by organizational goals and objectives as well as organizational knowledge and innovation. The Tawhidic approach contributes to the theoretical and practical understanding of the development of a unified theory of the firm.